THE ROLE OF THE CENTRAL JAVA PROVINCIAL WAGE COUNCIL IN DETERMINING REGENCY/CITY MINIMUM WAGES IN 2020 - AGUS PRAMONO (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
The purpose of the study entitled